Foreign exchange market interventions: A frequently used and effective tool - Lukas Menkhoff; Tobias Stöhr (DIW Economic Bulletin, 2017)
Is it common for central banks to intervene in foreign exchange markets in order to influence exchange rates? And if so, is it effective? From a German perspective, these questions seem surprising, since the European Central Bank (ECB) does not intervene in foreign exchange markets-rather, it lets the exchange rates float freely. The situation is very different in the emerging countries: according to the present analysis, central banks in these countries intervene in the foreign exchange market on almost one out of every three days. This study draws upon both confidential and publicly available data on foreign exchange market interventions from 33 countries- including industrialized, emerging, and developing countries-between 1995 and 2011. According to these data, central banks primarily bought foreign currencies to build foreign exchange reserves. The average intervention volume on days when interventions took place was close to 50 million USD; projected onto the GDP of the European Monetary Union, this would equal roughly two billion USD. On average, interventions lasted for five days, but could also be significantly shorter or longer. Most interventions were carried out against the existing exchange rate trends. Measured against the standard success measures-without taking control variables into account-interventions were successful in 60 to 90 percent of the cases. These success rates are significantly higher than the likelihood of these exchange rates improving on their own. FX interventions are thus a non-negligible tool when it comes to economic policy strategies.
Keywords: F31; F33; E58; 330; foreign exchange intervention; exchange rate regimes; effectiveness measures